Frequency of Cervical Lymph Node Extracapsular Spread in Oral Squamous Cell Carcinoma Patients - Abdullah Khan, Riaz Ahmed Warraich, Ashfaq-ur-Rahim, Sadiq Ali, Muhammad Nauman, Asif Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To estimate the frequency of cervical lymph node extracapsular spread in oral squamous cell carcinoma patients. Methodology: This prospective study was conducted in the Department of Oral and Maxillofacial Surgery, The University of Lahore from 1st December 2021 to 30th November 2022 and 50 diagnosed cases of oral squamous cell carcinoma were enrolled. Computed tomography scan was conducted for the diagnosis in addition to the histopathology of the samples. The CT scan images were used for identification of lymph node size, shape, and central necrosis. The frequency of the extracapsular extension of lymph nodes with the central necrosis was correlated with histopathology. Results: The mean age of the patients was 60.5± 11.1 years with 60% of the cases were males and 40% of the cases were females. 36% of those patients were having a history of smoking, 22% were having a history of taking pan, 14% supari & chalia, 8% alcoholics and 6% consuming gutka. The primary tumor site identified through clinical and diagnostic imaging was anterior 2/3rd of tongue in 38% followed by posterior 1/3rd of tongue in 20%, buccal mucosa 14%, mandible and lip each as 10%, maxilla 4%, floor of mouth and retromolar trigone region each as 2%. It was observed that T3 and T4 cases had more ECS than T1 and T2 with a percentage of 20% and 30% respectively. Practical implication: Knowledge of frequency and burden of this disease in Pakistan will assist in generating more efficient management and treatment protocols with early detection strategies of oral squamous cell carcinoma through association analysis and biomarker role of cervical lymph node extracapsular spread. Conclusion: Extracapsular spread is observed more in patients having advanced stage tumor or having advanced grade of oral squamous cell carcinoma. Key words: Extracapsular spread, Oral squamous cell carcinoma, Recurrence, Histopathological examination